Completing the “Nurses back to healthcare” training and returning to professional work: a qualitative study of nurses’ experiences - Kadri Kööp; Mare Tupits (BMC Nursing)
Abstract Background A substantial problem in the healthcare system is the lack of healthcare workers, especially nurses. An adequate number of nurses would reduce errors caused by work overload. The “Nurses back to healthcare” training is designed to alleviate the nursing shortage by providing an opportunity for nurses who are currently not working in the profession to re-enter healthcare. By reintegrating these experienced professionals, the programme helps to alleviate the nursing shortage, thereby improving patient outcomes and reducing strain on the existing workforce. Objectives To describe nurses’ experiences of completing the “Nurses back to healthcare” training and returning to professional work. Design A qualitative, empirical, and descriptive design. Participants The participants were nurses (N = 17) who completed the training. Methods Semi-structured interviews were conducted to collect data, and an inductive content analysis was performed to analyse data. Subject recruitment and data collection occurred concurrently until no new information emerged, indicating that saturation had been reached. Results The nurses’ experiences of completing the training included experiences with starting studies, satisfaction with the training, training-related challenges, the type of support received, and recommendations for improving the training. The experiences of returning to professional work included experiences related to job search, work reintegration, support, and considerations for work reintegration. All 17 participants indicated a generally positive assessment of the training. However, 6 participants considered the volume of theoretical knowledge too extensive, and 10 participants suggested increasing the volume of practical activities. Conclusions The “Nurses Back to Healthcare” training programme is essential in reintegrating nurses into the profession. Tailoring the programme to meet individual learning needs and adopting flexible approaches can significantly enhance its effectiveness. Participants with less professional experience and longer gaps since their studies require increased practice time, support in adapting to technological developments, and emotional support to address feelings of insecurity. Facilitating their transition back into the workforce also involves guiding them towards appropriate employment opportunities and offering flexible working conditions that consider their personal needs and prior experience.